Evaluation of Apple Root-Associated Endophytic Streptomyces pulveraceus Strain ES16 by an OSMAC-Assisted Metabolomics Approach - Armin, Reyhaneh; Zühlke, Sebastian; Mahnkopp-Dirks, Felix; Winkelmann, Traud; Kusari, Souvik (Frontiers in Sustainable Food Systems, 2021)
The One Strain Many Compounds approach (OSMAC) is a powerful and comprehensive method that enables the chemo-diversity evaluation of microorganisms. This is achieved by variations of physicochemical cultivation parameters and by providing biotic and abiotic triggers to mimic microorganisms' natural environment in the lab. This approach can reactivate the silent biosynthetic routes of specific metabolites typically not biosynthesized under standard laboratory conditions. In the present study, we combined the OSMAC approach with static headspace solid-phase microextraction-gas chromatography-mass spectrometry (SPME-GC-MS), high-performance liquid chromatography-high-resolution tandem mass spectrometry (HPLC-HRMSn), and matrix-assisted laser desorption/ionization high-resolution mass spectrometry imaging (MALDI-HRMSI) to evaluate the chemoecological significance of an apple root-associated endophytic Streptomyces pulveraceus strain ES16. We employed the OSMAC approach by cultivating the endophyte in six different media conditions and performed temporal studies over 14 days. Analysis of the volatilome revealed that only under stressful conditions associated with sporulation, endophytic S. pulveraceus ES16 produces geosmin, a volatile semiochemical known to attract the soil arthropods Collembola (springtails) specifically. Subsequently, targeted metabolic profiling revealed polycyclic tetramate macrolactams (PTMs) production by the endophyte under stress, which are bioactive against various pathogens. Additionally, the endophyte produced the iron-chelating siderophore, mirubactin, under the same conditions. The structures of the compounds were evaluated using HRMSn and by comparison with literature data. Finally, MALDI-HRMSI revealed the produced compounds' spatial-temporal distribution over 14 days. The compounds were profusely secreted into the medium after production. Our results indicate that endophytic S. pulveraceus ES16 can release the signal molecule geosmin, chemical defense compounds such as the PTMs, as well as the siderophore mirubactin into the host plant apoplast or the soil for ecologically meaningful purposes, which are discussed.